Unveiling parents’ lived experience with preterm infant care and support in neonatal care units of public hospitals in Nepal: A phenomenological inquiry - Tumla Shrestha; Archana Pandey Bista; Sarala Joshi Pradhan; Sangita Pudasainee-Kapri; Madhusudan Subedi (PLoS ONE, 2025)
Background Preterm infants (PTIs) require hospitalization in different levels of neonatal care units (NCUs) for their survival and developmental needs. The quality of care provided at NCUs significantly influences infant outcomes and parents’ experiences. Parents’ experience of received support and care of PTIs is one of the indicators for determining the quality of care at NCUs. The study aims to investigate parents’ perspectives on the PTIs care and support received from nurses in NCUs of Nepal. Methods A descriptive phenomenological study was conducted within the NCUs of three public tertiary hospitals in Kathmandu, Nepal. In-depth interviews were conducted among 25 purposively selected parents, (both mothers and fathers) of low-birthweight PTIs admitted to the NCUs. Data was collected from November 2019 to February 2020. The data were meticulously analyzed using the Colaizzi method. Findings The exploration of parents’ experiences identified three main theme areas: (1) Care and support, (2) Initial involvement in PTI care, and (3) Outcome of care involvement. Parents appreciated competent and affectionate PTI care as well as informational support. However, they had varied experiences with communication, emotional support, and opportunities for infant-parent attachment. Guidance and support for PTI care from nurses and peer-parents proved instrumental in mitigating uncertainties related to initial care learning and involvement in PTI care. Parents’ involvement in hands on care of their PTIs boosted infant-parent attachment, empowered for care giving, and provided emotional solace. Conclusion Findings indicate that parents have positive experience with PTI care provided by nurses and their involvement in hands-on care of their PTIs. However, there are gaps in support expectations of parents including communication, emotional support, and care guidance. Findings have important implications for nurses, pediatricians, and policymakers for the enhancement of neonatal care practice by incorporating parental support and parents’ involvement in hands on care of PTI across NCUs in Nepal.